AN EXPERIMENTAL STUDY OF THE FE-MN EXCHANGE BETWEEN GARNET AND ILMENITE - Feenstra A.; Engi M. (My University, 1998)
The exchange equilibrium was studied by reversal experiments as a function of temperature (650 ≤ T ≤ 1000 °C), pressure (10 ≤ P ≤ 20 kbar), and chemical composition. Experiments were performed in a piston-cylinder apparatus using starting mixtures consisting of 95% garnet and 5% ilmenite. At the lower temperatures, 3–5% PbO flux was added to the reactants. The PbO was reduced to metallic lead by the graphite of the capsules. The EMP analysis shows that ilmenite is essentially a solid solution of FeTiO3 and MnTiO3 with up to 4.5 mol% Fe2O3 (for Fe-rich compositions). Garnet is compositionally close to (Fe,Mn)3 Al2Si3O12 but apparently contains up to 1.0 wt% TiO2. As garnet was usually analyzed within 5–15 μm distance from ilmenite grains, the Ti measured in garnet appears to be largely an analytical artifact (due to secondary fluorescence). This was confirmed by analyzing profiles across a couple constructed from ilmenite and Ti-free garnet. The more than 100 exchange runs indicate that the distribution coefficient KD [=(X Mngnt·X Feilm)/(X Fegnt·X Mnilm)] is essentially independent of P and decreases with T. With a few exceptions at Mn-rich compositions, the present results are consistent with previous studies on the Fe-Mn partitioning between garnet and ilmenite. Contrary to previous studies, however, the narrow experimental brackets obtained during the present calibration constrain that, at constant T, KD is larger for Mn-rich compositions than for Fe-rich ones. This compositional dependence of KD will complicate garnet-ilmenite geothermometry. Mutually consistent activity models for Fe-Mn garnet and ilmenite, based on a thermodynamic analysis of the present results and other phase equilibria studies in the system Fe-MnO-Al2O3-TiO2-SiO2-O2, will be presented in a following contribution (M. Engi and A. Feenstra, in preparation).